2006
DOI: 10.22456/2177-0018.2113
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia paraendodôntica: revisão da literatura e apresentação de casos clínico-cirúrgicos

Abstract: INTRODUÇÃOA apicetomia é um procedimento cirúrgico considerado, em muitos casos, como último recurso para a manutenção de um elemento dentário. Desta forma, tem indicação quando a terapêutica endodôntica esgota as suas possibilidades. Além da remoção da lesão apical, visa a ressecção do ápice radicular, a eliminação dos microrganismos e zonas de imperfeição do pericemento apical e a verificação e/ou fechamento hermético deste. Os autores apresentam dois casos clínico-cirúrgicos em que a cirurgia paraendodôntic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 2 publications
0
15
0
7
Order By: Relevance
“…According to many authors, the incidence varies from 0.04 to 10% 1,3,[5][6][7][8][9] . This anomaly is caused by the folding of the dental papilla, which allows the invagination of the internal I and II 2,5,8,10,[15][16]18,[20][21]23 . Even when diagnosed and treated early, regular follow-up is necessary because the prognosis is not entirely favorable, as shown by Lucas et al 25 , who controlled 80 (13 type I and 67 type II) teeth clinically and radiographically for more than six months after closing the opening on the surface of the dental element early; nine (11.3%) treatments failed, all of them involving invagination type II.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to many authors, the incidence varies from 0.04 to 10% 1,3,[5][6][7][8][9] . This anomaly is caused by the folding of the dental papilla, which allows the invagination of the internal I and II 2,5,8,10,[15][16]18,[20][21]23 . Even when diagnosed and treated early, regular follow-up is necessary because the prognosis is not entirely favorable, as shown by Lucas et al 25 , who controlled 80 (13 type I and 67 type II) teeth clinically and radiographically for more than six months after closing the opening on the surface of the dental element early; nine (11.3%) treatments failed, all of them involving invagination type II.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment should only be performed when nonsurgical treatment fails 2,19 . Azambuja et al 21 reported a successful case where only surgical treatment was performed on a tooth with periapical radiolucency and no radiographic pulp chamber. One of the last measures to preserve the dental element is intentional dental reimplantation 1,5,10,15,16,20 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations